1997
DOI: 10.1103/physrevb.55.15874
|View full text |Cite
|
Sign up to set email alerts
|

X-ray reflectivity studies of liquid metal and alloy surfaces

Abstract: Surface-induced atomic layering at the liquid/vapor interface in liquid metals has been observed using x-ray reflectivity on sputtered clean surfaces under ultrahigh vacuum conditions. A well-defined quasi-Bragg peak is obtained for surfaces of elemental Ga and a Ga-In alloy at large wave vectors q z ϳ2.3-2.5 Å Ϫ1 . These results are an unambiguous indication of atomic layering with an interlayer spacing dϳ2/q z ϭ2.5-2.7 Å. For liquid Ga, the amplitude of the electron-density oscillations, which is significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
121
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 44 publications
7
121
0
Order By: Relevance
“…This surface layering was first verified experimentally at the liquid-air interfaces of Hg [3] and Ga [4] by x-ray reflectivity (XRR) measurements. Subsequent experimental studies demonstrated such layering also for numerous other liquid metals [4][5][6][7][8][9] and liquid metal alloys [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This surface layering was first verified experimentally at the liquid-air interfaces of Hg [3] and Ga [4] by x-ray reflectivity (XRR) measurements. Subsequent experimental studies demonstrated such layering also for numerous other liquid metals [4][5][6][7][8][9] and liquid metal alloys [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade XR revealed the long-predicted surface-induced atomic layering at the liquid-vapor interface for a number of elemental liquid metals [7][8][9][10][11]. Resonant XR near an absorption edge resolved the density profile of each component in GaIn [2], HgAu [3] and BiIn [4] liquid binary alloys. The enhancement of the concentration of the low-surfacetension component was invariably found to be confined to the topmost surface monolayer, with subsequent layers having the composition of the bulk, in accord with the simplest, and widely used, interpretation of the Gibbs rule.…”
mentioning
confidence: 99%
“…At ⌰ Ga = 5, the QS structure suddenly disappeared, and the typical depth of holes decreased to about 2.7 Å. This value is close to the distance between nearest neighbor atoms in bulk liquid Ga ͑2.56 Å͒ 19 and also the spacing between nearest atomic layers ͑2.5-2.7 Å͒ at liquidvapor interfaces of Ga, 12 In, 20 and eutectic In:Ga alloy, 12 suggesting formation of atomic layers with the 5 ϫ 5 structure and no trace of the ␣ -Ga͑001͒ structure.…”
Section: Growth Of Atomically Flat Nanofilms and Surface Superstructumentioning
confidence: 54%
“…11 During further growth of Ga, soluble In atoms diffuse into Ga, resulting in the formation of an outermost In ML. 12,13 To change the morphology of grown Ga from droplets to a flat film, the surface energy of Si ͑ Si Ϸ 1400 dyn/ cm at 30°C͒ 14 must be larger than the sum of energy of the film surface fs and energy of the Si-Ga interface Si-Ga . Segregation of In should reduce fs , since the surface energy of In ͓575 dyn/ cm ͑unnaturally assuming that it is liquid at 30°C͒ 15 and 650 dyn/ cm ͑solid͒ 16 ͔ is lower than that of Ga ͓718 dyn/ cm ͑liquid at 30°C 15 ͒ and 800 dyn/ cm ͑solid͒ 16 ͔.…”
Section: Growth Of Atomically Flat Nanofilms and Surface Superstructumentioning
confidence: 99%